The Effect of Health Education Program Based on Health Belief Model on Oral Health Behaviors in Pregnant Women of Fasa City, Fars Province, South of Iran - Jeihooni, Ali Khani (J Int Soc Prev Community Dent, 2017)
AIMS AND OBJECTIVES: Pregnant women are at risk of dental caries and periodontal disease. The purpose of this study was to assess the effectiveness of health education program based on health belief model (HBM) on oral and dental hygiene behaviors in pregnant women in Fasa city. MATERIALS AND METHODS: This is a clinical trial study carried out on 110 pregnant women selected using random sampling method from health centers in Fasa city in 2016 (55 patients in the experimental group and 55 individuals in control group). Data collection with questionnaire was based on construct HBM, as well as their performance about oral health. At first, two groups completed the questionnaires. And then, the intervention was conducted for the experimental group based on HBM. Four months after intervention, two groups completed the questionnaires twice. To analyze the collected data, the researchers used SPSS version 22 and descriptive and analytical statistics tests such as independent t-test and Chi-square and Mann–Whitney test. RESULTS: The age of the pregnant mothers was 28.25 ± 3.02 years in the experimental group and 27.8 ± 4.20 years in the control group. Compared to the control group, the experimental group showed a significant increase in their knowledge, perceived susceptibility, perceived severity, perceived benefits, self-efficacy, cues to action, and performance and decrease in perceived barriers 4 months after the intervention. CONCLUSION: Applying the HBM is very effective for developing an educational program for oral health in pregnant women. Moreover, in the implementation of these programs, control, monitoring, and follow-up educational are recommended.